Childlessness and upward intergenerational support: cross-national evidence from 11 European countries - Pesando, Luca Maria (Ageing Soc, 2018)
Childless individuals are often depicted as “selfish” as they opt out of raising children in favour of investing resources in themselves. Yet no research has investigated whether this claim holds in domains of social life such as intergenerational family support. Using data from the Generations and Gender Survey (GGS) for 11 European countries, this article examines differences between childless and non-childless individuals in the provision of financial, practical, and emotional transfers to their elderly parents. Results support the idea that the childless are more prone to providing upward support than individuals with children. Specifically, estimates from multivariate logistic regression and propensity score specifications suggest that, ceteris paribus, childless adults are about 20 to 40 per cent more likely to provide support to their parents, with the association driven by transfers to elderly mothers. These findings enrich the literature on childlessness and ageing, and support the view that researchers and policy makers should take into more consideration not only what childless people receive or need in old age, but also what they provide as middle-aged adults.